POLICY ANALYSIS OF TAX AMENDMENT AND TAX KNOWLEDGE ON TAXPAYER COMPLIANCE WITH PERSONAL PERSONS AT THE TAX SERVICE OFFICE PRATAMA GRESIK - Maria Felisitas Fitri; Aloisius Hama (Institute of Computer Science (IOCS), 2022)
The purpose of this study was to determine the effect of tax amnesty policy and knowledge of taxation. on the compliance of individual taxpayers at the Gresik Pratama Tax Service Office. This research is a type of quantitative descriptive research. The population of this research is tax amnesty policy, and knowledge of taxation. In this case, the unit of analysis is the individual taxpayers registered at KPP Pratama Gresik as many as 6,507 people, the total number of respondents in this study was 100 people. The analytical technique used in this research is multiple linear. Based on the results of research and submission of hypotheses to 100 individual taxpayers registered at the Gresik Pratama Tax Service Office, the following conclusions can be drawn: The better the tax amnesty policy implemented by the Indonesian government, the compliance of individual taxpayers will increase. Thus H1